The Role of Transformative Business Ecosystems in Pursuing sustainable Economy - the Case Oxygen2050 - Milla Wirén; Thomas Westerholm; Annika Liikamaa; Jari Ala-Ruona (Germany, 2022)
Social entrepreneurship (Mair & Marti, 2006; Zahra, Gedajlovic, Neubaum, & Shulman, 2009) and impact investment (Bugg-Levine & Emerson, 2011; Höchstädter & Scheck, 2015) have garnered interest especially in the realm of practitioners, and to an extent also among academics. Social entrepreneurs and impact investors have a twofold perspective to the global environmental and social problems: on the one hand they are intrinsically motivated to contribute to a ‘better tomorrow’, and on the other hand they view the problems as also business opportunities. These viewpoints also constitute a continuum between fully philanthropic activities and fully profit oriented activities (Brandstetter & Lehner, 2015; Sainio, 2018; Seymour, 2012), where the endpoints are populated at one end by NGOs and philantrophists, and at the other by traditional corporations and investors. The social entrepreneurs and impact investors populate various areas on the continuum, joined together by their belief in the possibility of combining the perspectives. In this article we cluster these entrepreneurs and investors under the label of ‘transformative business’. It is the aim of our research to explore the mechanism through which these aspirations embedded in the ideology of Oxygen 2050 may or may not be realized. As such, our research contributes to filling the lacunae in academic knowledge in two contemporary and relevant areas: first, we contribute to the understanding of the role of interorganizational and interindividual networks in tackling the ‘wicked problems’, and secondly we contribute to the nascent literatures of social entrepreneurship and impact investment from an ecosystem perspective. Our research question is simple: How does the value of transformative business ecosystems materialize?
36th European Group for Organizational Studies Colloquium (EGOS), University of Hamburg